Gender Role Stereotyping in Indonesian Primary School English Textbooks - Fadhila Yonata (Journal of English Education, 2021)
This study aims to examine gender role stereotyping represented in Indonesian primary school English textbooks. The categorization of roles are in the form of family roles, occupational roles, and activity. The data were taken from two English textbooks published by a private company commonly used by primary schools. By employing content analysis, the findings reveal dichotomy in family roles, domestic-tendency of occupational roles for female, and low-risk activity depicted in female characters. The implications of the study are discussed discursively to promote gender awareness at school context especially for teachers as authoritative users in the classroom and to recommend language textbook author and designer to dismiss gender role stereotyping.